1978
DOI: 10.1515/zna-1978-0305
|View full text |Cite
|
Sign up to set email alerts
|

Superstructures on Spherical Gold Crystals

Abstract: Spherically shaped crystals of gold were grown by solidification of a drop of melt in UHV. Their surfaces were investigated in situ by RHEED. The superstructures (001) (5x20) and (110) (1 X 2) were observed again. Further superstructures were found: on (001) vicinal planes, (227) (1 X 1), (111) (23 X 1) and (551)c(l X 1). Several of the new structures are related to structures already known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(25 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…In Figure 4, a high resolution STM image reveals significant surface corrugation that seems to agree well with the originally suggested (5 x 1) reconstruction (50) where the added rows run along the {100} direction. Since that time, various models have been put forward, and then later a (5 x 20) (63), a (5 x 20) with rotation (64), a c(26 x 68) (37) , (24 x 48) with rotation (65), and a hexagonal (28 x 5)R0.6° (66).…”
Section: Surface Structures Of Au Single Crystalsmentioning
confidence: 99%
“…In Figure 4, a high resolution STM image reveals significant surface corrugation that seems to agree well with the originally suggested (5 x 1) reconstruction (50) where the added rows run along the {100} direction. Since that time, various models have been put forward, and then later a (5 x 20) (63), a (5 x 20) with rotation (64), a c(26 x 68) (37) , (24 x 48) with rotation (65), and a hexagonal (28 x 5)R0.6° (66).…”
Section: Surface Structures Of Au Single Crystalsmentioning
confidence: 99%
“…Also on our spherical crystals of gold the well known structure (001)(5x20) was observed before we used the cleaning of Au by premelting it in air [15]. These crystals have shown also the known structure (110)( 1 x 2) and the new ones (11 l)(23x 1), (227)(1 x 1), (551)(1 x 1) and reconstructions on (001) vicinal planes [15], Later on the new structure (lll)(23xl) was confirmed by several authors on differently prepared specimens with different methods, as reported recently [16], Surprisingly the oxygen-cleaned Au crystals show only the naive structures (001 )(1 x 1) of Fig. 5 and (111)(1 X 1) [17], These results were confirmed on 5 crystals after melting in air only and on 8 crystals after premelting in air and remelting in UHV.…”
Section: Electron Diffraction: Surface Reconstructionsmentioning
confidence: 65%
“…Contrary to the naive surfaces of copper and silver, reconstructions on Au surfaces were observed by several authors (see [15]). Also on our spherical crystals of gold the well known structure (001)(5x20) was observed before we used the cleaning of Au by premelting it in air [15].…”
Section: Electron Diffraction: Surface Reconstructionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Contact UMI directly to order. (110) surface shows a (2x1) "missing row" reconstruction [3,7], and the (111) surface a ((22 ± 1) X \/3 [1, [8][9][10][11][12][13]] unit cell. A common feature of all reconstructions is that the topmost layer becomes denser.…”
mentioning
confidence: 99%